The 'Jalpama' Board Game Based on Pranata Mangsa Ethnoscience: a Solution to Optimize Students' Science Literacy - Lestari, Riska Yulia Ayu; Sayekti, Ika Candra (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aims to develop IPAS learning media in the form of a board game oriented towards contextual science concepts based on local wisdom and analyze the feasibility of the Jalpama board game media ethnoscience-based Pranata Mangsa to optimize science literacy of elementary school students. Methodology: The method used in this research is R&D through the ADDIE model and is limited to the media development stage. Data will be collected using interviews, documentation, and questionnaires using validation sheets. Data analysis techniques used qualitative and quantitative methods. Results: This research has the results of an ethnoscience-based board game media product called JALPAMA (Jejak Alam Pranata Mangsa), which includes natural resource preservation material as climate change mitigation by containing several game components, namely the game board, companion cards containing contextual information and questions about seasonal changes, natural resources and climate change, as well as supporting devices in the form of instructions for use, pawns, and dice. Based on the media feasibility test results, a percentage score of 91% was obtained, so the criteria for the JALPAMA board game media were said to be